Pengembangan Skala Cyberchondria Versi Pendek - Princen; Sugianto, Dicky; Simanjuntak, Erni Julianti (Journal of Research and Measurement in Psychology: JPPP, 2024)
This study aims to develop and validate a short version of the Cyberchondria Severity Scale (CSS). Exploratory Factor Analysis (EFA) was employed to identify the factor structure of the cyberchondria scale. The initial assumption tests indicated the scale's suitability for factor analysis (KMO > 0.5;